The Use of “KakAyu Dental Flipbook” in Oral Health Knowledge Improvement for Elementary School Students in Depok - Rikawarastuti, Rikawarastuti; Anggreni, Eka; Budiarti, Rahaju; Suid, Nurlaila Ramadhan (UI Scholars Hub, 2017)
Perlu adanya edukasi untuk meningkatkan pengetahuan anak Indonesia tentang pentingnya memelihara kesehatan gigi dan mulut. Penelitian ini bertujuan untuk menjelaskan hubungan antara faktor siswa sekolah dasar seperti kelas, usia, jenis kelamin dengan jumlah anak dalam keluarga atau faktor ekonomi seorang ibu rumah tangga atau berpenghasilan tetap, yang dipengaruhi oleh peningkatan pengetahuan dari edukasi kesehatan gigi dan mulut. Disain penelitian quasi experiment pre-test dan post-test tanpa desain grup kontrol melibatkan 141 siswa yang dipilih melalui purposive sampling. Sampel tersebar pada siswa kelas IV, V, dan VI sekolah dasar swasta di Depok, Jawa Barat, Indonesia pada April-Oktober 2016. Data penelitian diperoleh dari kuesioner pre-test dan post-test. Wilcoxon Signed Rank Test dan regresi logistik digunakan dalam pengolahan data. Hasil penelitian menunjukkan bahwa tingkat pengetahuan meningkat setelah dilakukan edukasi menggunakan “KakAyu Dental Flipbook”. Rata-rata hasil pengetahuan responden saat pre-test 80,85 ± 14,17 dan saat post-test 93,40 ± 9,84. Terdapat korelasi antara peningkatan pengetahuan dan edukasi menggunakan “KakAyu Oral Dental/Orthodonthic Flipbook” (nilai p = 0,001), namun tidak terdapat hubungan yang signifikan antara variabel (kelas, usia, jenis kelamin, jumlah anak dalam keluarga, dan status pekerjaan ibu) dengan peningkatan pengetahuan kesehatan mulut siswa sekolah dasar. Educating Indonesian children to improve their knowledge about the importance of maintaining oral health is needed. This study was aimed to explain relation between several factors in elementary school students, such as grade, age, sex with number of children in family or economic factor such as whether the mother is housewife or she earns regular income, which is affected by improvement of their oral health education. A quasi experiment pre-test and post-test without control group design involved 141 students as selected through purposive sampling. Samples were distributed to grade IV, V, and VI of private elementary school students in Depok, West Java, Indonesia in April-October 2016. Data collection used pre-test and post-test questionnaires. Data processing used Wilcoxon Signed Rank Test and regression logistic. Results showed the improvement of knowledge level after implementing “KakAyu Dental Flipbook” education. The average result of respondents’ knowledge at pre-test was 80.85 ± 14.17, and 93.40 ± 9.84 at post-test. There is a relation between knowledge improvement and education using “KakAyu Oral Dental/Orthodonthic Flipbook” (p value = 0.001), but no significant relation between the variables (grade, age, sex, number of family members and mother’s working status) and oral health knowledge improvement of elementary school students.